Propriety Analysis by Excluding Education from the Definition of 'Service' in the Consumer Protection Law at Buddhist Colleges - Rida Jelita (Syntax Idea)
Consumers are King is a paradigm that has been accepted by the general public for a long time. According to Law No. 8/1999, consumer protection is defined as all efforts to ensure legal certainty to provide protection for consumers. However, the implementation of consumer protection in the Buddhist College (STAB), has not received attention. In fact, somewhat neglected. This article discusses the results of research on consumer protection for students at STAB. This research uses the Normative Legal Research method. Starting with identifying the consumer protection aspect for STAB students ideally provided by education providers. The results of the study indicate that the views of students on consumer protection are very important to be given and applied at STAB